The mechanisms and roles of melatonin in gastrointestinal cancer - Gong, Yong-Qiang; Hou, Fu-Tao; Xiang, Cai-Ling; Li, Cheng-Long; Hu, Guo-Huang; Chen, Chao-Wu (Frontiers in Oncology, 2022)
Gastrointestinal (GI) cancer is a global health problem with wide lesions and numerous cases. The increased morbidity and mortality of GI cancer is a socio-economic challenge for decades to come. Melatonin, a nature indolamine, exerts a crucial role in molecular interactions involved in multiple functional and physiological processes. Increasing evidence indicates that melatonin can modulate GI tract, decrease the occurrence of GI cancer, and enhance the sensitivity to chemoradiotherapy. However, little is known about the exact role of melatonin in anti-carcinogenesis. In this review, we discuss the action of the beneficial effects of melatonin in GI carcinogenesis. Furthermore, we compile the understanding of the role of melatonin in GI cancer, including esophageal cancer (EC), gastric cancer (GC), hepatocellular carcinoma (HCC), colorectal cancer (CRC), and pancreatic cancer (PC). In addition, the potential therapeutic application and clinical evaluation of melatonin in GI cancer are also discussed.